Vaginal delivery after caesarean section and its associated factors in Mizan Tepi University Teaching Hospital, Southwest Ethiopia - Yeabsira Girma (Elsevier, 2021)
Background: Vaginal birth after caesarean section is appropriate for a majority of women who have had a single prior lower segment caesarean section. However, little is known about vaginal birth after caesarean section in Ethiopia. Thus, this study aimed to assess the success rate of vaginal birth after caesarean section and its associated factors in Mizan-Tepi University Teaching Hospital, southwest Ethiopia in 2020. Methods: An institutional-based cross-sectional study was conducted among 416 mothers who gave birth by caesarean section from 2017 to 2019. The data were entered into epidata version 3.1.0 and analysed by SPSS version 21.0. Multivariable logistic regression analysis was performed to identify the factors associated with successful vaginal birth after caesarean section. A crude and adjusted odds ratio with a 95% confidence interval was used to interpret the results. A P value of <0.05 indicated statistically significant results. Results: Of 416 completed charts reviewed, the success rate of vaginal birth after cesarean section was 170 (41%), with 95% CI (36.2%, 45.6%). The factors associated with successful vaginal birth after cesarean section were: macrosomia as past indication of cesarean section delivery: AOR; 0.31, 95% CI (0.15, 0.62); prior successful vaginal birth after cesarean section: AOR; 2, 95% CI (1.18, 3.70); previous successful spontaneous vaginal delivery: AOR; 4, 95% CI (2.05, 7.83); cervical dilatation at admission: AOR; 2.7, 95% CI (1.47, 4.95), and duration of labor: AOR; 1.7, 95% CI (1.07, 2.83). Conclusion: The success rate of vaginal birth after caesarean section in the study area was low. Macrosomia as past indication of caesarean section, prior vaginal birth after caesarean section, history of vaginal birth, cervical dilatation at admission, and duration of labour were significantly associated with the success rate. Emphasis should be placed on those factors that lead to a higher likelihood of successful vaginal birth.